PROSPECTS OF INCORPORATING THE CONCEPT OF PROGRAMMING CONSUMER EXPERIENCES IN THE RESTAURANT BUSINESS - ANTOSHKONA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The relevance of the chosen research topic is due to the need to find new ways of developing the restaurant business in the conditions of modern challenges. The restaurant business plays an important social, image and economic role in the development of the national economy, acts as a supporting component of tourism and creates jobs for a significant number of the population.In the conditions of the СOVID-19 pandemic, the restaurant business faced a number of new and unpredictable problems that stopped the dynamic development of the industry and required the development of new strategic solutions for adaptation in transformational conditions. The existence of a direct relationship between the evaluation of the quality of the service received and the customer's repeat visit to the restaurant confirmed the feasibility of incorporating the concept of programming customer impressions to acquire a positive emotional experience and exceed consumer expectations. The basis for the introduction of the concept of programming consumer impressions should be the understanding of the restaurant business owners of the psychological characteristics and needs of individuals in acquiring a positive emotional experience.The implementation of consumer impression programming technologies at restaurant enterprises will allow to achieve mutual agreement between the value positions of customers and the enterprise, determine the space for ensuring the unity of their expectations, and as a result will ensure the growth of loyalty. Therefore, the introduction of the concept should include such a complete knowledge of the habits, intentions, preferences and needs of its customers that allows the company to create and offer a personalized approach to each customer, which will encourage them not only to remain loyal, but also to play the role of an active communication channel for attraction of new customers.
Keywords: restaurant business; customer orientation; experience programming; consumer; loyalty; emotional experience